Dekolonialisasi Pendidikan: Studi Kritis Hegemoni Keilmuan Barat di Pesantren Modern - Dwi Jaka Anandika Kutsi; Zainal Arifin (University of Muhammadiyah Malang, 2023)
This study examines the dominance of Western knowledge in the education system of modern Islamic boarding schools (pesantren) in Indonesia and proposes decolonization to strengthen local cultural and intellectual identities. The influence of globalization is reflected in the adoption of curricula that integrate Western values and knowledge, which, while aiming to enhance educational quality, often neglect local cultural values and identities. This situation potentially leads to the erosion of Islamic cultural identity. Colonialism in education manifests in two forms: structural, involving physical dominance and political control, and cultural, encompassing ideological and cultural dominance through educational institutions. Gramsci's Cultural Hegemony Theory elucidates how the dominant class propagates its culture and ideology, as seen in the dominance of Western knowledge within modern pesantren. This research aims to evaluate the impact of integrating local knowledge into the pesantren curriculum on student outcomes and to identify effective decolonization strategies within Islamic education in Indonesia. The goal is to create a pesantren education system that is more inclusive and respectful of local cultural identities and Islamic knowledge, free from the dominance of Western values and methodologies. Using a literature review method, this study concludes that emphasizing decolonization strategies in the modern pesantren curriculum is essential for strengthening local cultural identities and equipping students with critical and creative thinking skills without losing their cultural identity